A Conceptual Framework of Data (Info) Quality Revisited. Issue 1 (13th October 2021) - Stewart, Brenton; Ju, Boryung
Abstract: This study reports a critical assessment of whether the framework of data (information) quality identified by Wang and Strong's (1996) seminal article continues to hold true in a diverse 21st century information environment. Our study attempts to identify the salient changes that have taken place since Wang and Strong's analysis by exploring wiki contributors' perceived information quality on Wikipedia. An online qualitative survey was conducted with 197 respondents who are Wikipedia readers and/or contributors. Our preliminary results from the unidimensional data analysis reveal over 20 information quality dimensions including a new category, with multiple dimensions.